Correlation Between Serum miR-154-5p and Osteocalcin in Males and Postmenopausal Females of Type 2 Diabetes With Different Urinary Albumin Creatinine Ratios - Ren, Huiwen; Ma, Xiaoyu; Shao, Ying; Han, Jinyu; Yang, Min; Wang, Qiuyue (Frontiers in Endocrinology, 2019)
Purpose: To investigate the serum levels of miR-154-5p, osteocalcin (OC), and other clinical parameters in male and postmenopausal female type 2 diabetes mellitus (T2DM) patients with different urinary albumin creatinine ratio (UACR) levels and to discuss the relationship between miR-154-5p and glycolipid metabolism, bone metabolism, and different urinary albumin excretion rate in T2DM. Methods: Seven hundred thirty-eight T2DM patients were categorized into six groups, including 374 men and 364 postmenopausal women who were sub-divided into three groups based on albumin excretion that involved normal albuminuria, microalbuminuria and large amount of albuminuria (138, 127, 109, 135, 125 and 104 cases, UACR<30 mg/g, 30-300 mg/g and >300 mg/g, M1, M2, M3, F1, F2 and F3). Measurement of circulating miR-154-5p, OC, and other biochemical indicators were performed by real-time PCR, ELISA, and chemiluminescence assays in T2DM patients and in 141 M0 and 139 F0 control subjects. Results: There are few differences appeared between groups. Comparing with men, women had higher age, waist-to-hip ratio (WHR), adiponectin (ADPN), connective tissue growth factor (CTGF), UACR, procollagen type 1 N-terminal propeptide (P1NP), β-C-terminal telopeptide of type I collagen (β-CTx), OC, and miR-154-5p, but lower FPG, HOMA-IR and HbA1c. T2DM patients with albuminuria (micro or macro) had lower bone turnover markers (P1NP, β-CTx and OC) and adiponectin, but higher HbA1c, CTGF, and miR-154-5p. In addition, after regression analysis, UACR was positively correlated with CTGF, HbA1c and miR-154-5p, and negatively correlated with ADPN and bone turnover markers (P1NP, β-CTx, and OC). However, OC showed a positive correlation with ADPN and other bone turnover markers (P1NP and β-CTx), but negative correlation with CTGF, UACR and miR-154-5p in all three groups. Conclusion: These findings suggested that increased serum levels of miR-154-5p and decreased OC levels may influence osteogenesis and proteinuria in T2DM and may identify novel targets for diagnosis and treatment of diabetic kidney disease and osteoporosis.